2011
DOI: 10.4088/jcp.10m06497
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) on Prescribing Practices

Abstract: We found some evidence in our sample that the publication of the results from CATIE had a small but statistically significant effect on prescribing habits of psychiatrists but not other physicians in our sample population. However, larger changes occurred in prescribing behavior that were largely unrelated to the CATIE trial. We propose a hypothesis to explain the direction of observed changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…As expected, there was no appreciable change in the utilisation pattern for risperidone vs. other atypical antipsychotic drugs following the availability of generic risperidone (Figures and , Table ). This may well reflect the advice from NICE and the conclusions of the various Cochrane reviews and CATIE studies that treatments should be tailored to the individual as schizophrenia and bipolar disease are far more complex to treat than diseases treated with the PPIs, statins, ACEIs or ARBs. Consequently, there is no apparent Hawthorne effect .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As expected, there was no appreciable change in the utilisation pattern for risperidone vs. other atypical antipsychotic drugs following the availability of generic risperidone (Figures and , Table ). This may well reflect the advice from NICE and the conclusions of the various Cochrane reviews and CATIE studies that treatments should be tailored to the individual as schizophrenia and bipolar disease are far more complex to treat than diseases treated with the PPIs, statins, ACEIs or ARBs. Consequently, there is no apparent Hawthorne effect .…”
Section: Discussionmentioning
confidence: 82%
“…These debates have continued with the publication of the various findings from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study in the US showing limited differences between the various antipsychotic drugs, although this is not without criticism . Various studies suggest that ‘the numerous antipsychotic drugs, however they might be classified, are more similar to than different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…These debates have continued with the publication of the various findings from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study in the US showing limited differences in effectiveness between the various antipsychotics, although this is not without criticism (Lieberman et al, 2005; Lieberman and Stroup, 2011; Wladysiuk et al, 2011; Berkowitz et al, 2012). The studies do show though that the variation in the effectiveness of the different AAPs can be substantial between individual patients, and that side-effects can also differ between different AAPs (Lieberman and Stroup, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of laboratory claims data collected between 2001 and 2006 showed that the warning was not associated with an increase in glucose testing among patients receiving atypical antipsychotic treatment and was associated with only a marginal increase in lipid testing rates. However, there was a decline in prescriptions for olanzapine, which has a high metabolic risk of AEs, and an increase in prescriptions for aripiprazole, a low metabolic risk antipsychotic [38][39][40] . It should be noted, however, that aripiprazole was approved by the FDA for the indication of schizophrenia during the study period (2002), which may confound the results.…”
Section: Commentarymentioning
confidence: 97%